Varicella-Zoster Meningitis in an Immunocompetent Male without Fever or Rash - Raju Raghunathan; Qasim Khalil; Mohamad Mooty (Case Reports in Infectious Diseases)
Varicella-Zoster virus (VZV) is a human herpesvirus that primarily causes chickenpox and can reactivate later in life. Chickenpox occurs mostly in children and is characterized by a typical generalized vesicular rash. Following the primary infection, VZV can remain latent and can reactivate decades later to produce Zoster, being more common in the elderly as well as immunosuppressed individuals. The diagnosis of both the primary and reactivation is mostly clinical from the typical rash. However, when presentations are atypical, it leads to diagnostic challenges. We report an unusual case of VZ reactivation in an immunocompetent young adult presenting without fever, zoster rash, or neuralgia. The diagnosis was established by a positive polymerase chain reaction (PCR) performed on cerebrospinal fluid samples. The patient was treated with acyclovir and responded very well. The diagnosis of VZ meningitis is challenging in the absence of typical features of Zoster rash and requires a high index of suspicion.